Chitinase improves the available energy, amino acids digestibility of black soldier fly and fecal microbiota of growing pigs - Yuansen Yang; Shenrui Xu; Wenjun Gao; Yu Wei; Lu Wang; Changhua Lai (Animal Bioscience)
Objective The main objective of this study was to determine the energy value and digestibility of amino acids in growing pigs fed black soldier fly (BSF) with chitinase supplementation and its effect on fecal microbiota. Methods In Exp. 1, eighteen barrows with initial body weight (BW) of 31.6±1.2 kg were randomly assigned to 3 treatments to determine the digestible energy (DE), metabolizable energy (ME), and nutrient digestibility, including the corn-soybean meal basal group, the BSF (14.6%) with 1,500 mg/kg or without chitinase groups. Fresh feces were collected on day 10 of feeding for analysis of microbial diversity. In Exp. 2, six barrows (36.7±4.2 kg BW) with ileal T-cannulas were arranged in a 6×3 Youden square design, pigs were allotted to 3 dietary treatments to determine the digestibility of the amino acids, including the nitrogen-free group, the BSF with or without chitinase groups. Results Supplemental chitinase improved (p<0.05) the apparent total tract digestibility (ATTD) of crude protein and dry matter in the BSF diet, improved (p<0.05) the ATTD of crude protein, ether extract and acid detergent fiber in the BSF, and increased the BSF's DE and ME by 2.34 MJ/kg and 1.37 MJ/kg, respectively. Chitinase supplementation improved (p<0.05) the composition of fecal microbiota of growing pigs, promoted (p<0.05) the colonisation of Bacilli, Lactobacillaceae, and Lactobacillales, and inhibited (p<0.05) the proliferation of pathogenic bacteria Sarcina. Adding chitinase enhanced the apparent ileal digestibility and standardized ileal digestibility of most amino acids in BSF, such as methionine, leucine, and glutamate (p<0.05). Conclusion Adding chitinase can increase the effective energy value and amino acid ileal digestibility of BSF, regulate the composition of fecal microbiota and improve the intestinal health of growing pigs.